Effects of Dehydration on Brain Perfusion and Infarct Core After Acute Middle Cerebral Artery Occlusion in Rats: Evidence From High-Field Magnetic Resonance Imaging - Tsai, Yuan-Hsiung; Yang, Jenq-Lin; Lee, I-Neng; Yang, Jen-Tsung; Lin, Leng-Chieh; Huang, Yen-Chu; Yeh, Mei-Yu; Weng, Hsu-Huei; Su, Chia-Hao (Frontiers in Neurology, 2018)
Background: Dehydration is common among ischemic stroke patients and is associated with early neurological deterioration and poor outcome. This study aimed to test the hypothesis that dehydration status is associated with decreased cerebral perfusion and aggravation of ischemic brain injury. Methods: Diffusion-weighted imaging and arterial spin labeling perfusion MR imaging were performed on rats with middle cerebral artery occlusion (MCAO) by using a 9.4T MR imaging scanner to measure the volume of infarction and relative cerebral blood flow (rCBF) after infarction. Twenty-five rats were assigned to either a dehydration group or normal hydration group, and dehydration status was achieved by water deprivation for 48 hours prior to MCAO. Results: The volume of the infarction was significantly larger for the dehydration group at the 4th hour after MCAO (p = 0.040). The progression in the infarct volume between the 1st to 4th hours was also larger in the dehydration group (p = 0.021). The average rCBF values of the contralateral normal hemispheres at the 1st and the 4th hour were significantly lower in the dehydration group (p = 0.027 and 0.040, respectively). Conclusions: Our findings suggested that dehydration status is associated with the progression of infarct volume and decreases in cerebral blood flow during the acute stage of ischemic stroke. This preliminary study provided an imaging clue that more intensive hydration therapies and reperfusion strategies are necessary for the management of acute ischemic stroke patients with dehydration status.